2016
DOI: 10.1016/j.joca.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Body composition is more closely related to the development of knee osteoarthritis in women than men: a cross-sectional study using the Fifth Korea National Health and Nutrition Examination Survey (KNHANES V-1, 2)

Abstract: In women, high fat mass and low lower extremity muscle mass were associated with presence and severity of knee OA. Lower extremity muscle mass was more closely correlated with knee OA than obesity in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 46 publications
3
41
1
1
Order By: Relevance
“…Yet another cross‐sectional study found increasing odds of knee OA with increasing quartiles of BMI and fat mass, but no association was found with lower extremity muscle mass . In the same study, obese subjects with a low percentage of lower extremity muscle mass (comparable to sarcopenic obese subjects in our study) and nonobese subjects with a low percentage of lower extremity muscle mass (comparable to sarcopenic subjects in our study) were found to have greater odds of radiographic OA compared with nonobese subjects with normal lower extremity muscle mass.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Yet another cross‐sectional study found increasing odds of knee OA with increasing quartiles of BMI and fat mass, but no association was found with lower extremity muscle mass . In the same study, obese subjects with a low percentage of lower extremity muscle mass (comparable to sarcopenic obese subjects in our study) and nonobese subjects with a low percentage of lower extremity muscle mass (comparable to sarcopenic subjects in our study) were found to have greater odds of radiographic OA compared with nonobese subjects with normal lower extremity muscle mass.…”
Section: Discussionsupporting
confidence: 60%
“…The few previous studies that have examined the association of body composition with knee OA have found conflicting results . Issues with study design and lack of consistency in definition of obesity and sarcopenia from body composition assessment (i.e., fat and muscle mass) partly explain discordant results.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of KNHANES V 1–2, a total of 6,567 households selected from 384 survey regions responded to the questionnaire-based survey and were categorized by region, gender, age, and average household size. The details of the KNHANES V have been previously described elsewhere [1, 17, 18]. This cross-sectional study used data from the fifth KNHANES V 1–2 (N = 17,476; performed from January 2010 to December 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Obesity influences OA not only by increasing weight loads on the knee joints, but also by adipose tissue working as a source of inflammation . Body composition represented as fat mass, rather than body weight, is more important and closely related to knee OA . Adipose tissue releases adipokines, which enhance catabolic factors and lead to the synovial inflammation and structural damage of OA …”
Section: Discussionmentioning
confidence: 99%